The alternative law of alternative dispute resolution - Woodman, Gordon (Les Cahiers de droit, 1991)
The perceptions afforded by the study of legal pluralism assist an understanding of the full scope and the social and moral significance of alternative dispute resolution. The latter term includes all modes and forms of dispute resolution within the legal order of the state other than the usual forms of adjudication by the ordinary courts. These modes may be classified in relatively wide and fluid categories as other forms of adjudication, and arbitration, mediation and negotiation. However, alternative dispute resolution also includes instances of all these processes which are not established, adopted, or made effective by the state. The study of legal pluralism throughout the world shows that almost everywhere are many such instances, generated within many semi-autonomous social fields other than the state, and falling into all the listed categories. The study of legal pluralism further suggests that the different dispute settlement processes are likely to be associated with different bodies of legal norms. There is evidence that to some extent alternative state processes employ different bodies of laws. The evidence also shows that non-state processes employ bodies of norms which always differ, and may differ widely from those of state law. While legal centralism denies these norms the name of "laws", there seems no good reason not to classify such rules and principles, which order relations within social fields other than the state, as "customary law", or by some similar term. Alternative dispure resolution processes have been lauded as enhancing the effectiveness of the law, providing wider access to justice or law. However, if the argument presented here is correct, it is not sufficient to represent them as implementing "the law". Rather each implements a different variety of law. The social functions of these different laws of different dispute resolution processes, both state and non-state, vary, and so need investigation in each particular case. Whether any law is to be approved as affecting power relations in the society concerned is similarly a matter for investigation. While it has been suggested that alternative dispute resolution processes can confer on the weak and underprivileged an opportunity to assert their interests, it has been argued against such a view that they may provide opportunities for the already powerful to increase their powers, free of the restraining influence of regular state courts. On the other hand, state processes may at certain historical moments be manipulated by the weak to their advantage. Non-state processes may, also in special circumstances, empower collectively the members of the social fields in which they operate.